2021
DOI: 10.1017/s1368980021000306
|View full text |Cite
|
Sign up to set email alerts
|

COVID-washing of ultra-processed products: the content of digital marketing on Facebook during the COVID-19 pandemic in Uruguay

Abstract: Objective: To explore the use of references to the COVID-19 pandemic as part of the marketing strategies used on Facebook to promote ultra-processed products. Design: A search for Facebook accounts of ultra-processed products was performed using a master list of products commercialized in two online supermarkets in Uruguay. For each of the identified Facebook accounts, all the content posted from the confirmation of the first cases of COVID-19 in Uruguay, on March 14th, 2020, until July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 38 publications
1
31
0
3
Order By: Relevance
“…Food baskets containing ultra-processed products with excessive content of sugar, fat and sodium were identified, mainly when the organisations received donations from the food industry. The ultra-processed food industry has made donations to communities as part of their strategic responses during COVID-19 pandemic (53,54) . These donations are often regarded as a contribution to food security.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food baskets containing ultra-processed products with excessive content of sugar, fat and sodium were identified, mainly when the organisations received donations from the food industry. The ultra-processed food industry has made donations to communities as part of their strategic responses during COVID-19 pandemic (53,54) . These donations are often regarded as a contribution to food security.…”
Section: Discussionmentioning
confidence: 99%
“…These donations are often regarded as a contribution to food security. However, they are also part of the marketing strategies of the food industry as they enable the distribution and promotion of products close to expiration date in the context of reduced sales to the most vulnerable populations (53,54) . Therefore, it seems necessary to develop strategies to discourage inclusion of ultra-processed products with excessive content of nutrients associated with non-communicable diseases as part of the foods provided by civil society in the context of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the lockdown period that emerged with the Covid-19 pandemic encouraged more online shopping and fostered a digital marketing environment that was easily exploited. Antúnez et al (2021) found that the COVID-19 pandemic helped industries of ultra-processed products quickly promote their goods, create positive associations with their brands, and improve their brand image through their digital strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the lockdown period that emerged with the Covid‐19 pandemic encouraged more online shopping and fostered a digital marketing environment that was easily exploited. Antúnez et al (2021) found that the COVID‐19 pandemic helped industries of ultra‐processed products quickly promote their goods, create positive associations with their brands, and improve their brand image through their digital strategies. As a reflection of the severe influence of the COVID 19 pandemic on children, such as being exposed to marketing from unhealthy products more often and rising obesity and junk food consumption problems (Ertz & Le Bouhart, 2021), many issues have emerged in this literature recently.…”
Section: Introductionmentioning
confidence: 99%
“…Drastic changes in the business environment affected by Covid-19 (Bairizki et al, 2021), resulting in MSMEs experiencing a decline in sales and some unable to survive being forced to close their businesses, The transition phase of the pandemic to the normal phase causes changes in consumer behavior (Antúnez et al, 2021)namely a decrease in purchasing power and changes in lifestyle that are increasingly paying attention to the halalness, benefits and cleanliness of food products. In this condition, MSMEs are experiencing a post-pandemic transition period.…”
Section: Introductionmentioning
confidence: 99%